The bruising of Qilwa - Jamnia, Naseem (Tachyon Publications, 2022)
Firuz-e Jafari was able to escape the slaughter of traditional blood magic practitioners by immigrating to the city-state of Qilwa. But now a terrible disease is spreading through the city, and Firuz believes it comes from ineptly performed blood magic. Now they must find a way to break a cycle of prejudice in order to survive.